Household investment under violence : the Colombian case - Grun, Rebekka (Policy research working paper, 2008)
"Households in rural Colombia are confronted with a variety of violent threats: attacks and displacement threats by guerrillas and paramilitaries, gang violence among drug traffickers, and high common delinquency. In this context, households have to adjust their day-to-day decisions, including saving and portfolio choices, in order to be less vulnerable. The authors test the hypothesis that households, when confronted with exogenous violence, reduce their investment and, moreover, shift it from fixed to mobile assets, which would be safer in the case of displacement, and choose the opposite strategy under higher common delinquency associated with property crimes. Empirical evidence from a rich Colombian micro-data set strongly supports the hypothesis. The results shed new light on the economic impact of violence. The immediate reduction in capital stock might be much less severe than more permanent damage via the savings function. This has implications for the appropriate political answer to chronic violence in Colombia as well as in other areas of chronic conflict. "--World Bank web site